Proceso de ASC - IMPLICACIONES ETICAS DE LA IMPLEMENTACION DE LA INTELIGENCIA ARTIFICIAL EN EL PROCESO JURISDICCIONAL (2021)
Ethical implications of implementing artificial intelligence in the judicial process are critically examined. This raises questions regarding the ethical consequences of applying artificial intelligence and using related technologies, particularly concerning impartiality, judicial independence, and the requirement to provide reasoning for judicial decisions as a manifestation of the fundamental rights to due process and effective judicial protection.